0184 Mortality profile of the French cohort of uranium processing workers. (23rd June 2014) - Samson, Eric; Piot, Irwin; Zhivin, Sergey; Acker, Alain; Laroche, Pierre; Laurier, Dominique
Abstract : Objectives: A cohort of nuclear workers employed in the fuel processing cycle was set-up in France in 2009 to assess the risk of cancer and non-cancer mortality related to uranium, in a context of occupational multi-exposure. Vital status and causes of death are now available. Method: The cohort includes workers employed at least 6 months between 1958 and 2006 by AREVA and CEA (French Atomic Energy Commission). Exposure assessment was realised by a dual approach combining individual monitoring data and specific job-exposure matrices, considering radiation exposures, chemical agents and physical stresses (heat and noise). Additional information like tobacco consumption and various clinical parameters (Body Mass Index, blood pressure, lipid profile etc.) was also collected from the Occupational Health Services. Vital status and causes of death were collected from French national registries. Results: The cohort includes 12 739 workers (88% men) with an average duration of employment of 17 years. The median year of birth is 1944. At the end of follow-up (31/12/2010), 19% are deceased and 96% of the causes of death are identified. Cancers (mainly lung, prostate and lymphatic and haematopoietic tissue cancers) represent 43% of all causes of death, non-cancers (mainly diseases of the circulatory system) 48% and external causes 9%. The analyses using French national mortality rates as reference will be presented. Conclusions: The observed mortality is that of an even young population and at this stage no further conclusions can be drawn. This cohort, with this wealth of data, will be very informative for the investigation of uranium related risks.